Right to land use of public enterprises (Journal of actual problems of jurisprudence, 2018)
The article offers analysis the legislation on the ground, on state property of Land. Given the law enforcementpractices regarded the legal status of state legal entities in land use.Keywords: subject of state property right, land use, the authority of the authorized state body.